Related Recurrence Relations

Algebra Level 5

Let a n a_n , b n b_n , and c n c_n satisfy the system of recursive relations below for n 2 n \geq 2 :

{ b n 2 n 2 = c n 1 c n 2 3 a n 2 2 n 3 + a n 1 5 a n 2 = 2 b n 1 + c n 2 c n 6 a n 2 + 5 a n 1 = a n 2 n 2 \large \begin{cases} b_n - 2^{n-2} = c_{n-1} - c_{n-2} - 3a_{n-2} \\ 2^{n-3} + a_{n-1} - 5a_{n-2} = 2b_{n-1} + c_{n-2} \\ c_n - 6a_{n-2} + 5a_{n-1} = a_n - 2^{n-2} \end{cases}

If a 0 = 5 a_0 = 5 , a 1 = 10 a_1 = 10 , b 0 = 259 48 b_0 = -\frac{259}{48} , b 1 = 65 8 b_1 = -\frac{65}{8} , c 0 = 7 4 c_0 = \frac{7}{4} , and c 1 = 3 2 c_1 = \frac{3}{2} , find the value of a 7 + b 5 c 6 a_7 + b_5c_6 .

This problem is part of the set " Xenophobia "


The answer is 4672.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Marco Brezzi
Aug 15, 2017

Rearranging

{ b n = c n 1 c n 2 3 a n 2 + 2 n 2 c c i i c c c ( 1 ) a n 1 = 2 b n 1 + c n 2 + 5 a n 2 2 n 3 c c c ( 2 ) c n = a n + 6 a n 2 5 a n 1 2 n 2 c c c c c c c ( 3 ) \begin{cases} b_n=c_{n-1}-c_{n-2}-3a_{n-2}+2^{n-2} \phantom{cciiccc} (1)\\ a_{n-1}=2b_{n-1}+c_{n-2}+5a_{n-2}-2^{n-3} \phantom{ccc} (2)\\ c_n=a_n+6a_{n-2}-5a_{n-1}-2^{n-2} \phantom{ccccccc} (3) \end{cases}

We can increase/decrease every indices/exponent that depends on n n by the same amount without changing the recurrence. Increasing by 1 1 in ( 2 ) (2)

{ b n = c n 1 c n 2 3 a n 2 + 2 n 2 c c i c ( 1 ) a n = 2 b n + c n 1 + 5 a n 1 2 n 2 c c i i c ( 2 ) c n = a n + 6 a n 2 5 a n 1 2 n 2 c i c i c ( 3 ) \begin{cases} b_n=c_{n-1}-c_{n-2}-3a_{n-2}+2^{n-2} \phantom{ccic} (1)\\ a_{n}=2b_{n}+c_{n-1}+5a_{n-1}-2^{n-2} \phantom{cciic} (2)\\ c_n=a_n+6a_{n-2}-5a_{n-1}-2^{n-2} \phantom{cicic} (3) \end{cases}

Now, with 2 ( 1 ) + ( 2 ) + ( 3 ) 2(1)+(2)+(3) we get

2 b n + a n + c n = 2 ( c n 1 c n 2 3 a n 2 + 2 n 2 ) + 2 b n + c n 1 + 5 a n 1 2 n 2 + a n + 6 a n 2 5 a n 1 2 n 2 2b_n+a_n+c_n=2(c_{n-1}-c_{n-2}-3a_{n-2}+2^{n-2})+2b_{n}+c_{n-1}+5a_{n-1}-2^{n-2}+a_n+6a_{n-2}-5a_{n-1}-2^{n-2}

Simplifying like terms

c n = 3 c n 1 2 c n 2 c_n=3c_{n-1}-2c_{n-2}

Using the auxiliary polynomial to find the closed form

p ( t ) = t 2 3 t + 2 p(t)=t^2-3t+2

Its roots are t = 1 t=1 and t = 2 t=2 , so c n c_n is of the form

c n = λ 1 + λ 2 2 n c_n=\lambda_1+\lambda_22^n

Using the given values of c 0 c_0 and c 1 c_1

{ c 0 = λ 1 + λ 2 = 7 4 c 1 = λ 1 + 2 λ 2 = 3 2 λ 1 = 2 , λ 2 = 1 4 \begin{cases} c_0=\lambda_1+\lambda_2=\dfrac{7}{4}\\ c_1=\lambda_1+2\lambda_2=\dfrac{3}{2} \end{cases} \Longrightarrow \lambda_1=2,\lambda_2=-\dfrac{1}{4}

c n = 2 2 n 2 \Longrightarrow c_n=2-2^{n-2}

Substituting back in ( 3 ) (3) and simplifying like terms

a n = 5 a n 1 6 a n 2 + 2 a_n=5a_{n-1}-6a_{n-2}+2

To find the closed form of a n a_n I'll use a generating function

A ( x ) = k = 0 a k x k = a 0 + a 1 x + k = 2 a k x k = 5 + 10 x + k = 2 ( 5 a k 1 6 a k 2 + 2 ) x k = 5 + 10 x + 5 k = 2 a k 1 x k 6 k = 2 a k 2 x k + k = 2 2 x k = 5 + 10 x 5 a 0 x + 5 x k = 1 a k 1 x k 1 6 x 2 k = 2 a k 2 x k 2 + 2 x 2 1 x = 5 15 x + 5 x A ( x ) 6 x 2 A ( x ) + 2 x 2 1 x \begin{aligned} A(x)&=\sum_{k=0}^{\infty} a_kx^k\\ &=a_0+a_1x+\sum_{k=2}^{\infty} a_kx^k\\ &=5+10x+\sum_{k=2}^{\infty} (5a_{k-1}-6a_{k-2}+2)x^k\\ &=5+10x+5\sum_{k=2}^{\infty} a_{k-1}x^k-6\sum_{k=2}^{\infty} a_{k-2}x^k+\sum_{k=2}^{\infty} 2x^k\\ &=5+10x-5a_0x+5x\sum_{k=1}^{\infty} a_{k-1}x^{k-1}-6x^2\sum_{k=2}^{\infty} a_{k-2}x^{k-2}+\dfrac{2x^2}{1-x}\\ &=5-15x+5xA(x)-6x^2A(x)+\dfrac{2x^2}{1-x} \end{aligned}

From which we get

A ( x ) = 5 15 x + 2 x 2 1 x 6 x 2 5 x + 1 A(x)=\dfrac{5-15x+\dfrac{2x^2}{1-x}}{6x^2-5x+1}

By partial fractions and Taylor series of 1 1 x \dfrac{1}{1-x}

A ( x ) = 3 1 2 x + 1 1 3 x + 1 1 x = k = 0 ( 3 2 k + 3 k + 1 ) x k \begin{aligned} A(x)&=\dfrac{3}{1-2x}+\dfrac{1}{1-3x}+\dfrac{1}{1-x}\\ &=\sum_{k=0}^{\infty} (3\cdot 2^k+3^k+1)x^k \end{aligned}

a n = 3 2 n + 3 n + 1 \Longrightarrow a_n=3\cdot 2^n+3^n+1

By substitution in ( 1 ) (1) we can get the closed form of b n b_n

b n = c n 1 c n 2 3 a n 2 + 2 n 2 = 2 2 n 3 ( 2 2 n 4 ) 3 ( 3 2 n 2 + 3 n 2 + 1 ) + 2 n 2 = 33 2 n 4 3 n 1 3 \begin{aligned} b_n&=c_{n-1}-c_{n-2}-3a_{n-2}+2^{n-2}\\ &=2-2^{n-3}-(2-2^{n-4})-3(3\cdot 2^{n-2}+3^{n-2}+1)+2^{n-2}\\ &=-33\cdot 2^{n-4}-3^{n-1}-3 \end{aligned}

To summarize

{ a n = 3 2 n + 3 n + 1 b n = 33 2 n 4 3 n 1 3 c n = 2 2 n 2 \begin{cases} a_n=3\cdot 2^n+3^n+1\\ b_n=-33\cdot 2^{n-4}-3^{n-1}-3\\ c_n=2-2^{n-2} \end{cases}

Thus

a 7 + b 5 c 6 = 3 2 7 + 3 7 + 1 + ( 33 2 5 4 3 5 1 3 ) ( 2 2 6 2 ) = 2572 + ( 150 ) ( 14 ) = 4672 \begin{aligned} a_7+b_5c_6&=3\cdot 2^7+3^7+1+(-33\cdot 2^{5-4}-3^{5-1}-3)(2-2^{6-2})\\ &=2572+(-150)(-14)=\boxed{4672} \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...